Pensar la informática cuántica. - Alejandro Yanover, David (Chasqui (13901079), 2007)
The article looks at ideas and innovations concerning quantum computing. Quantum computing has to do with the behind the scenes efforts in digital processing as well as creating new advances and possibilities for computers. Details are included about the evolution of computer technology and possibilities for the future. The article gives information about computer companies such as Intel and computer bits as well as programming of software. The author also takes a look at Moore's Law, which is used in describing the trend of computer hardware over the years.